Preparation and Characterization of a Stable Nano-Sized ZnxCo1 – xAl2O4 Ink for Glass Decoration by Ink-jet Printing - Peng, Xiaojin; Zhang, Qi; Cheng, Jinshu; Yuan, Jian; Wu, Ya; Jie, Junnan (MAIK Nauka/Interperiodica (МАИК Наука/Интерпериодика), 2017)
A stable inorganic glass ink was prepared by mechanically grinding a mixture of a blue pigment(ZnxCo1 – xAl2O4) and low-melting-point glass powders in a specific organic solvent, which possesses a lower annealing temperature compared with ceramic ink. The ZnxCo1 – xAl2O4 based pigment was synthesized by solid-state reaction and the best sintering temperature should be at 1300°C or above according to the observation of XRD. ZnxCo1 – xAl2O4 shows blue color both in a powder form and coating. The average particle size of pigments and glass powders mixture decreases with the increase of glass powders and milling time. SEM cross-sectional images of annealed coating samples illustrate that the pigments are well dispersed in the ink layer and the glass adhesive binds well on the surface of glass plate, enhancing the mechanical strength of the ink layer. All the obtained results collectively revealed that the prepared nano-sized ZnxCo1 – xAl2O4 ink can be applied in glass decoration.
Keywords: Nano-CoAl2O4 ink; Preparation; Characterization; Ink-jet; Glass decoration